The Effect of Providing People's Business Credit (Kur) Bri Palattae Unit on Increasing the Income of MSMEs in Lalepo Village, Kahu District, Bone Regency - Juhardi (Journal AGENCY, 2023)
This research aims to find out whether the provision of BRI Palattae People's Business Credit (KUR) has an effect on increasing MSME income in Lalepo Village, Kahu District, Bone Regency." This research was conducted in Lalepo village, Kahu District, Bone Regency over a period of 2 (two) months from April to May 2022. The type of research used in this research is quantitative research. The quantitative research method was chosen based on the philosophy of positivism, which is used to research certain populations or samples, with the aim of testing predetermined hypotheses. This research is quantitative research using a multiple linear regression model which is processed using the SPSS v16.0 for Windows application. Based on the results of the t test calculation (partial), the t-count value was 3.801 and the t-table was 2.014 with a significance level of 0.000. Because the t-calculated value is greater than the t-table with a significance smaller than 0.05 (5%), the results of this study indicate that the provision of People's Business Credit (KUR) at Bank Rakyat Indonesia Palattae Unit has a positive and significant effect on increasing income. MSMEs in Lalepo Village, Kahu District, Bone Regency amounted to 21.5%, while the remaining 78.5% were influenced by other variables which were not included in this research.